RANCANG BANGUN SISTEM INFORMASI MANAJEMEN BANK SAMPAH DENGAN METODE EXTREME PROGRAMMING - Luluk Suryani; Raditya Faisal Waliulu; Ery Murniyasih; Imam Trianggoro Saputro; Sonny Rumalutur; Marcelinus Petrus Saptono (Electro Luceat, 2022)
The implementation of the Garbage Bank program is strived to be able to provide benefits and economic value from waste management, its existence is expected to have a direct impact on the people's economy so that it can be implemented easily. The Sorong Raya Garbage Bank (BSSR) has 108 Unit Waste Banks, 3,131 Customers, so it is only appropriate for BSSR to have an integrated management information system to support its business processes and operations. So far, BSSR management has not run optimally, because data loss often occurs, each division and level has data that is out of sync, difficulty finding data due to inconsistent writing and flow, the resulting reports are not optimal so that it has an impact on decision making. The research will be conducted using the extreme programming method. The output of this research is a waste bank management information system that can help BSSR integrate the management of each division and level so that business and operational processes can run effectively and efficiently. The system will be designed using the Unified Modeling Language (UML). System testing will use the Black Box method. The results of the black box test state that the input and output of the Sorong Raya Garbage Bank Management Information System are appropriate.